2020
DOI: 10.1021/acs.jafc.0c04833
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Patterns of Zinc and Iron Accumulation during Barley (Hordeum vulgare L.) Grain Development

Abstract: Breeding and engineering of biofortified crops will benefit from a better understanding of bottlenecks controlling micronutrient loading within the seeds. However, few studies have addressed the changes in micronutrient concentrations, localization, and speciation occurring over time. Therefore, we studied spatial patterns of zinc and iron accumulation during grain development in two barley lines with contrasting grain zinc concentrations. Microparticle-induced-X-ray emission and laser ablation-inductively cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Because free iron is cytotoxic, iron in these small bodies may be bound to citrate or nicotianamine (NA). A pool of Fe-citrate was found in aleurone cells of mature wheat grains using XANES imaging (De Brier et al, 2016;Pongrac et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because free iron is cytotoxic, iron in these small bodies may be bound to citrate or nicotianamine (NA). A pool of Fe-citrate was found in aleurone cells of mature wheat grains using XANES imaging (De Brier et al, 2016;Pongrac et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of iron in biological materials has been visualised using histological staining, X-ray fluorescence (XRF), micro-proton induced X-ray emission (µ-PIXE) and laserablation inductively coupled plasma mass spectrometry (LA-ICP-MS). When applied to cereal grains, these techniques (>10 µm resolution) showed accumulation of iron in the crease, the aleurone layer and the scutellum of the embryo in wheat (Neal et al, 2013;Singh et al, 2013;De Brier et al, 2016) and a similar pattern in other cereals (Iwai et al, 2012;Takahashi et al, 2009;Detterbeck et al, 2020). Nanoscale Secondary Ion Mass Spectrometry (NanoSIMS) has also become a significant tool to visualise minerals at the subcellular level due to its unique capabilities of high spatial resolution (50 nm), high sensitivity (ppm and ppb for some elements) and detection of trace elements and isotopes (for example see Malherbe et al, 2016;Kopittke et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…When associated with X-ray absorption spectroscopy, synchrotron-based approaches also provide information about metal micronutrient speciation together with the localization data ( Escudero et al , 2020 ) and can be used to analyze the efficiency of micronutrient fertilization ( Ajiboye et al , 2015 ). Other imaging techniques based on mass spectrometry, such as secondary ion mass spectroscopy (SIMS), laser ablation inductively coupled plasma-mass spectrometry (LA-ICP-MS), or matrix-assisted laser desorption/ionization (MALDI) imaging, have been used to reveal micronutrient localization ( Moore et al , 2018 ; Detterbeck et al , 2020 ). They provide isotopic information allowing dynamic analysis after isotopic labeling and, in some cases, allow in situ analysis of metal complexes.…”
Section: Overview Of Current Knowledge and Future Challenges For Rese...mentioning
confidence: 99%
“…Therefore, a thorough understanding of wheat grain physiology of Zn accumulation and distribution during grain filling is needed in order to produce cultivars with a higher level of grain Zn. In barley, Detterbeck et al (2020) revealed that Zn was evenly spread in grain tissues except within the embryo and vascular tissues at 7DAA, where Zn was present in a few patches. Furthermore, the crease region and the aleurone layer had a higher concentration of Zn at 27DAA, while the distribution of Zn in the grain compartments at this stage was similar to the localisation of Zn at maturity.…”
Section: Redistribution Of Zn Within the Grainmentioning
confidence: 99%